The unicorn and the lake - Mayer, Marianna; Hague, Michael (New York Dial Books for Young Readers, 1982)
When a serpent poisons the lake where all the animals drink, only the unicorn has the power to save them.
Keywords: Unicorns -- Fiction; Snakes -- Fiction